2013
DOI: 10.1254/jphs.12r14cp
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Regulation of Neuropathic Pain

Abstract: Abstract. Neuropathic pain is a highly debilitating chronic pain state that is a consequence of nerve injury or of diseases such as diabetes, cancer, infection, autoimmune disease, or trauma. Neuropathic pain is often resistant to currently available analgesics. There is a rapidly growing body of evidence indicating that signalings from spinal microglia play crucial roles in the pathogenesis of neuropathic pain. After peripheral nerve injury, microglia transform to reactive states through the expression of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 52 publications
5
66
0
2
Order By: Relevance
“…Activation of microglia occurs in most pathological processes, which is often accompanied by morphologic change and production of cytotoxic molecules, and upregulation of phagocytosis and immune surface antigens [8][9][10]. Activation of microglia is also involved in the pain transmission pathway of acute and chronic pains such as neuropathic pain, inflammatory pain and cancerous pain [11][12][13]. It has been found that the activated spinal microglia release bioactive molecules including interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α), nitric oxide (NO), and brain-derived neurotrophic factor (BDNF), which aggravate the range and duration of pain [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of microglia occurs in most pathological processes, which is often accompanied by morphologic change and production of cytotoxic molecules, and upregulation of phagocytosis and immune surface antigens [8][9][10]. Activation of microglia is also involved in the pain transmission pathway of acute and chronic pains such as neuropathic pain, inflammatory pain and cancerous pain [11][12][13]. It has been found that the activated spinal microglia release bioactive molecules including interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α), nitric oxide (NO), and brain-derived neurotrophic factor (BDNF), which aggravate the range and duration of pain [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies indicate that microglia can function as key players in the modulation of neuronal network excitability [2]. Furthermore, neuropathic pain pathogenesis depends on both changes in the activity of neuronal systems as well as microglia activation [3]. During the pathogenesis of neuropathic pain, resident microglia become activated [4], exhibiting up-regulation of the expression of cell surface receptors (including purinergic receptors and CD11b) [5,6], enhanced migratory ability [7] and pro-inflammatory cytokine release (including tumor necrosis factor (TNF)-α and brain-derived neurotropic factor (BDNF)) [8,9], which can enhance synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that neuropathic pain is associated with activation of spinal glial cells including microglia and astrocytes (2 -5). Microglia in the spinal cord rapidly respond to peripheral nerve injury and become in the active state (6), enabling them to send signals to astrocytes (7). Activated microglia and astrocytes secrete various biologically active pronociceptive mediators including proinflammatory cytokines and chemokines, which lead to hyperexcitability of spinal dorsal horn neurons (8).…”
Section: Introductionmentioning
confidence: 99%